A 6-year study on the mortality dynamics of sprouts germinated on Schima superba after a severe ice storm in southern China - Cao, Yonghui; Zhou, Benzhi; Wang, Xiaoming (Frontiers in Plant Science, 2023)
Introduction Natural disturbances modify forest structure by affecting regeneration dynamics and can change main ecosystem functions. An ice storm unusually took place in southern China in early 2008, which caused huge damage to forests. Resprouting of woody plants in a subtropical forest has received little attention. The role of survival time and mortality has been assessed for newsprouts after an ice storm. Methods In this study, damage types, in addition to the annual number and mortality rates of sprouts for all tagged and sampled resprouted Chinese gugertree (Schima superba Gardner & Champ.) individuals more than or equal to 4 cm in basal diameter (BD), were monitored. A total of six plots (20 m × 20 m) wererecorded in a subtropical secondary forest dominated by S. superba in Jianglang Mountain, China. This investigation had been conducted for six consecutive years. Results The results showed that the survival rates of the sprouts were dependent on the year they sprouted. The earlier the year they boomed, the lower the mortality. The sprouts produced in 2008 were of the highest vitality and survival rates. Sprouts of the decapitated trees exhibited a better survival rate than those of uprooted or leaning trees. Sprouting position also plays a role in regeneration. Sprouts at the basal trunks of uprooted trees and the sprouts at the upper trunksof the decapitated trees exhibited the lowest mortality. The relationship between the accumulative mortality rate and the average diameter of new sprouts isaffected by damage types. Discussion We reported the mortality dynamics of sproutsin a subtropical forest after a rare natural disaster. This information could serve asa reference for the construction of a branch sprout dynamic model ormanagement of forest restoration after ice storms.